Measurement of the ratio of branching fractions B (B+c→J [psi] [tau] + [nu] [tau])/B(B+c→J/[psi] [mu] + [nu] [mu]) - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; Han, Xiaoxue; et al. (Physical review letters, 2018)
A measurement is reported of the ratio of branching fractions R(J/ψ)=B(B+c→J/ψτ+ντ)/B(B+c→J/ψμ+νμ), where the τ+ lepton is identified in the decay mode τ+→μ+νμ¯ντ. This analysis uses a sample of proton-proton collision data corresponding to 3.0 fb−1 of integrated luminosity recorded with the LHCb experiment at center-of-mass energies of 7 and 8 TeV. A signal is found for the decay B+c→J/ψτ+ντ at a significance of 3 standard deviations corrected for systematic uncertainty, and the ratio of the branching fractions is measured to be R(J/ψ)=0.71±0.17(stat)±0.18(syst). This result lies within 2 standard deviations above the range of central values currently predicted by the standard model.
published 23 March 2018; corrected 4 April 2018
Im Titel sind "+" hochgestellt, "mu" und "tau" tiefgestellt
Im Titel sind "+" und "c" untereinander geschrieben: "+" hochgestellt, "c" tiefgestellt
Im Titel werden psi, tau, mu und nu als griechische Buchstaben dargestellt
R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, M. De Cian, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere] (LHCb Collaboration)